Temporal Viral Genome-Protein Interactions Define Distinct Stages of Productive Herpesviral Infection - Jill A. Dembowski (American Society for Microbiology, 2018)
ABSTRACT Herpesviruses utilize multiple mechanisms to redirect host proteins for use in viral processes and to avoid recognition and repression by the host. To investigate dynamic interactions between herpes simplex virus type 1 (HSV-1) DNA and viral and host proteins throughout infection, we developed an approach to identify proteins that associate with the infecting viral genome from nuclear entry through packaging. To accomplish this, virus stocks were prepared in the presence of ethynyl-modified nucleotides to enable covalent tagging of viral genomes after infection for analysis of viral genome-protein interactions by imaging or affinity purification. Affinity purification was combined with stable isotope labeling of amino acids in cell culture (SILAC) mass spectrometry to enable the distinction between proteins that were brought into the cell by the virus or expressed within the infected cell before or during infection. We found that input viral DNA progressed within 6 h through four temporal stages where the genomes sequentially (i) interacted with intrinsic antiviral and DNA damage response proteins, (ii) underwent a robust transcriptional switch mediated largely by ICP4, (iii) engaged in replication, repair, and continued transcription, and then (iv) transitioned to a more transcriptionally inert state engaging de novo-synthesized viral structural components while maintaining interactions with replication proteins. Using a combination of genetic, imaging, and proteomic approaches, we provide a new and temporally compressed view of the HSV-1 life cycle based on input genome-proteome dynamics. IMPORTANCE Herpesviruses are highly prevalent and ubiquitous human pathogens. Studies of herpesviruses and other viruses have previously been limited by the ability to directly study events that occur on the viral DNA throughout infection. We present a new powerful approach, which allows for the temporal investigation of viral genome-protein interactions at all phases of infection. This work has integrated many results from previous studies with the discovery of novel factors potentially involved in viral infection that may represent new antiviral targets. In addition, the study provides a new view of the HSV-1 life cycle based on genome-proteome dynamics.